THE ROLE OF MATHEMATICAL TERMINOLOGY IN FOLK PROVERBS: A COGNITIVE AND LINGUOCULTURAL ANALYSIS OF UZBEK AND ENGLISH PROVERBS - Nuridinova Dilinura Khamzayevna (International Journal of Literature and Language Studies, 2026)
This article examines the role of mathematical terminology in Uzbek and English folk proverbs from cognitive and linguocultural perspectives. Mathematical concepts such as numbers, quantity, measure, proportion, calculation, and comparison function not only as numerical indicators but also as cultural symbols reflecting collective experience and national worldview. The study aims to identify the semantic, cognitive, and linguocultural functions of mathematical terms in proverbs and reveal similarities and differences between Uzbek and English linguistic cultures. The research employs comparative, descriptive, cognitive-semantic, and linguocultural methods. The findings demonstrate that mathematical terminology in folk proverbs serves as an important mechanism for conceptualizing social relationships, moral values, labor activities, and life experiences. Numbers frequently acquire symbolic meanings beyond their mathematical functions, reflecting cultural traditions and national mentality. The analysis confirms that mathematical terminology acts as a cultural code preserving and transmitting collective knowledge across generations.